Styles of Coating with Stress and Psychological Well-Being in Teenagers - Urbano Reaño, Edira Yelitze (2022)
The relationship between the styles of coping with stress and psychological well-being is explored in a group of school teenagers (n = 237), aged 16 and 17, belonging to a school of leaders. The stress coping styles questionnaire and the psychological well-being scale were used. The results indicate that minimal practice of problem-focused coping styles are inversely related to high psychological well-being; while, minimal development of emotion-focused and additional stress-coping styles are related to low development of psychological well-being.